Elemental profile of native lichens displaying the impact by agricultural and artificial land uses in the Atlantic island of São Miguel (Azores) - Bernardo, Filipe (2021)
Smaller oceanic islands, often hosting endangered native habitats, are particularly vulnerable to the impact of human activities. Using lichens as bioindicators, this study aimed to test if agricultural (AGR) and artificial (ART) land uses are noticeably more impacted than forest (FOR) land use on an oceanic island (São Miguel, Azores). Livestock and farming practices in AGR areas involve the intensive application of synthetical agrochemicals as well as organic fertilizers and manure. ART areas accommodate vehicular traffic besides industries dedicated to waste management, energy production or exploration and transformation of raw materials. Naturally occurring Parmotrema lichens were collected in 28 sampling sites distributed between each land use. The concentrations of 58 elements as well as the percentage (%N) and the isotopic composition of nitrogen (δ15N) were determined on lichen samples. An overall pattern of significant elemental enrichment was observed in lichens from AGR and ART sites compared with FOR lichens, including several rare-earth elements. FOR lichens were noticeably cleaner, thus providing background concentrations for the calculation of bioaccumulation ratios. Bioaccumulation levels were generally low to moderate in AGR lichens and moderate to high in ART lichens, including toxic heavy metals. %N was highest in AGR lichens and its isotopic signature was distinguishable from ART lichens by significantly lower δ15N values. This study provides a comprehensive baseline of bioaccumulation data across major land uses for comparison with other insular regions, highlighting the greater vulnerability of island ecosystems to anthropogenic impacts even if by relatively small-scale human activities.